Influence of the catalyst type (TiO2 and ZnO) on the photocatalytic oxidation of pharmaceuticals in the aquatic environment. Issue 3 (14th January 2016) - Bohdziewicz, Jolanta; Kudlek, Edyta; Dudziak, Mariusz
Abstract: In recent years, an increasing interest in the new group of contaminants appearing in the aquatic environments i.e. pharmaceuticals and personal care products has been observed. The effect of the long-term exposure of living organisms to sufficiently lower the concentration of pharmaceuticals, which are found to be highly reactive, is still unknown. In addition with no toxicological data of pharmaceuticals action on living organisms, including humans, their constant elimination from water dedicated to human consumption is required. In this article, the efficiency of chosen pharmaceutical compounds via photocatalysis process is discussed. The photolysis process was also performed in order to compare both solutions. Titanium dioxide (TiO2 ) and zinc oxide (ZnO) were used as catalysts. The photocatalytic process was also evaluated according to the toxic effect of the purified water by means of MICROTOX ® analysis. The impact of the pharmaceutical concentration and oxidation time on the water samples toxicity has also been investigated. The highest efficiency of the process was revealed at the presence of TiO2 . The removal rate of pharmaceutical compounds reached 90%. It was additionally found that the radiation of water containing ZnO resulted in the generation of toxic byproducts, which significantly decreased the quality of purified water.